2022
DOI: 10.3390/ijms23031523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Pannexin 1 (PANX1) Channel Mechanosensitivity and Its Pathological Roles

Abstract: Pannexins (PANX) were cloned based on their sequence homology to innexins (Inx), invertebrate gap junction proteins. Although there is no sequence homology between PANX and connexins (Cx), these proteins exhibit similar configurations. The PANX family has three members, PANX1, PANX2 and PANX3. Among them, PANX1 has been the most extensively studied. The PANX1 channels are activated by many factors, including high extracellular K+ ([K+]e), high intracellular Ca2+ ([Ca2+]i), Src family kinase (SFK)-mediated phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…This rapid Ca 2þ amplification mechanism is shared by many cell types, including endothelial cells [11], cholangiocytes (epithelial cells) [12], and erythrocytes [13]. More likely than not it explains Panx1's apparent mechanosensitivity [14]. Of note, Panx1 also amplifies and relays GPVI signals to P2X1 in platelets [15].…”
Section: Mechanosensing Of Membrane Stretchingmentioning
confidence: 99%
“…This rapid Ca 2þ amplification mechanism is shared by many cell types, including endothelial cells [11], cholangiocytes (epithelial cells) [12], and erythrocytes [13]. More likely than not it explains Panx1's apparent mechanosensitivity [14]. Of note, Panx1 also amplifies and relays GPVI signals to P2X1 in platelets [15].…”
Section: Mechanosensing Of Membrane Stretchingmentioning
confidence: 99%
“…9,51 The elevated extracellular K + level contributes to ATP release by activating the pannexin-1 (Panx1) hemichannels. 52,53 It creates a vicious cycle that results in the continuous efflux of K + ions. 54 Several studies have suggested an association between reduced intracellular K + levels and NLRP3 activation, but the mechanistic link remains poorly understood.…”
Section: Activation Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…Also, the dead or dying cells in the ischemic area passively release ATP. This extracellular ATP activates the purinergic receptors (P2X4 and P2X7) on nearby cells, resulting in K + ion efflux. , The elevated extracellular K + level contributes to ATP release by activating the pannexin-1 (Panx1) hemichannels. , It creates a vicious cycle that results in the continuous efflux of K + ions . Several studies have suggested an association between reduced intracellular K + levels and NLRP3 activation, but the mechanistic link remains poorly understood.…”
Section: Low Intracellular Potassium (K+) Ions or K+ Effluxmentioning
confidence: 99%
“…It is well known that Panx‐1 operates as a damage‐associated molecular pattern (DAMP) molecule in the regulation of ATP release. As a result, extracellular ATP concentration increase due to cellular damage or stress through the Panx‐1 ion channel (Yang et al., 2022). Subsequently, extracellular ATP activates the P2X7 receptor, resulting in the NLRP3 activation and triggering an inflammatory response (Pelegrin, 2021).…”
Section: Introductionmentioning
confidence: 99%